2017
DOI: 10.1080/09540105.2017.1332007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between aerial parts and roots (Astragali Radix) of astragalus membranaceus by NMR-based metabolomics

Abstract: Aerial parts of Astragalus membranaceus (APAM), which are derived from the overground part of Astragalus membranaceus consist of stems and leaves. The aim of this study was to provide a scientific basis for the comprehensive utilization of APAM. Nuclear magnetic resonance (NMR) was used to compare the chemical compositions of APAM and Astragali Radix (AR). The pharmacological effects of APAR and AR in cyclophosphamide (Cy)-induced mice were studied using 1 H NMR-based metabolomics. The results showed that APAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In the present study, a new UPLC-Qtrap HRMS method was developed to identify the secondary metabolites in APAM and AR, and a 1 H NMR-based metabolomics was used to examine the pharmacological effects of APAR and AR in N-acetyl phenylhydrazine (APH) and Cy-treated mice. In combination with our previous study (Wang, Jin, et al, 2017), the results of this study are expected to contribute significantly to the establishment of a scientific basis for the comprehensive utilization of APAM.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the present study, a new UPLC-Qtrap HRMS method was developed to identify the secondary metabolites in APAM and AR, and a 1 H NMR-based metabolomics was used to examine the pharmacological effects of APAR and AR in N-acetyl phenylhydrazine (APH) and Cy-treated mice. In combination with our previous study (Wang, Jin, et al, 2017), the results of this study are expected to contribute significantly to the establishment of a scientific basis for the comprehensive utilization of APAM.…”
Section: Introductionsupporting
confidence: 56%
“…Glutamate is an intermediate product of glutamine metabolism (Wang, Jin, et al, 2017) and may affect the immune response of monocytes/macrophages, the proliferation of lymphocytes, and the synthesis of Hsp70 (Exner et al, 2003). Glutathione (GSH), a tripeptide of glutamate, glycine, and cysteine, is an efficient antioxidant that provides protection against oxidative stress, either by serving as a cofactor for some antioxidant enzymes or by reducing reactive oxygen species (ROS) (Lu, 2013;Roth et al, 2002;Yuan & Kaplowitzc, 2009).…”
Section: D-glutamine and D-glutamate Metabolismmentioning
confidence: 99%
“…Taking the distribution of flavonoids and saponins in different parts of Astragalus membranaceus plant as an example, previous reports showed that the AMSL was mainly comprised of flavonoids like isoflavones and flavones, while the root as the medicinal part contained the most of saponins, followed by flavones (Li et al, 2019; Shi, Bi, & Shi, 2018). Although the AMSL and the root of Astragalus membranaceus are different from each other in primary and secondary metabolites, they gave a similar performance in terms of immune functions (Wang et al, 2017) and the recovery of body weight, blood parameters, and viscera indices in Kunming mice (Wang, Liu, et al, 2019; Wang, Xu, et al, 2019), which implies that the AMSL is an excellent resource worthy of comprehensive utilization. So far, the studies on the potential application of AMSL are mainly focused on the extensive form like the livestock and poultry breeding (Abdallah, Zhang, Elemba, Zhong, & Sun, 2020; Xi et al, 2014), and the research on the intensive development and utilization of AMSL is scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…22,24,25 Currently, plant metabolomics has explored different states of AR. [26][27][28][29] Further, Yu et al 14 used a logistic regression algorithm to predict the quality class of AR, but the algorithm had difficulty adapting to the distribution of real nonlinear data and the quantitative data of only five differential components identified were not sufficiently representative of AR. In contrast, extreme learning machine (ELM) aims to train a single hidden layer feedforward neural network; it is faster than traditional learning algorithms with guaranteed learning accuracy.…”
Section: Introductionmentioning
confidence: 99%